Flexible TiN/Ge photodetectors with enhanced responsivity via localized surface plasmon resonance and strain modulation - Kim, You Jin (2023)
Near infrared (NIR) photodetectors (PDs) have attracted great attention for their applications in the field of optical telecommunication. Ge is one of the most attractive materials for the active region of the NIR PDs due to complementary metal oxide semiconductor (CMOS) compatibility and lower bandgap energy compared to those of Si. However, they suffer from significantly reduced responsivity in the wavelength region above 1.55 μm. Here, we develop a new scheme to boost the responsivity of Ge PDs by integrating TiN and Ge on flexible platforms. Responsivity is further modified by controlling the bandgap energy via applying various tensile and compressive strains. TiN is used as a responsivity booster, showing improvement of 63% compared to flat Ge PDs due to increased absorption via plasmon resonance and reduced reflection on the surface. Moreover, a further increase in responsivity is achieved by applying 0.30% tensile strain in the active region, reaching a responsivity of 11.5 mA W−1 at 1.55 μm. This work provides an efficient way to enhance the responsivity of flexible Ge PDs via heterogeneous integration of dissimilar materials.